Screen printed electromechanical micro-total analysis system (μtas) for sensitive and rapid detection of infectious diseases - Nordin, Anis Nurashikin; Zainuddin, Ahmad Anwar; Ab Rahim, Rosminazuin; Voiculescu, Ioana R.; Mak, Wing Cheung (Elsevier B.V., 2017)
The main objective of this article is to demonstrate by performing simulation measurements of biosensor that can detect the presence of pathogens through simultaneous mass and impedance techniques. This biosensor merges two biosensing techniques namely resonant frequency measurements and electrochemical impedance spectroscopy (EIS) on a single biosensor. Parallel measurements provide better sensitivities, have higher diagnostics accuracy and reduce the risk of false positives. Low cost, high resolution screen printing technology was used to fabricate the microelectromechanical array of μTAS on flexible piezoelectric substrates. The basic biosensor framework includes a substrate that highly sensitive sensor like thickness shear mode and immunosensor can be fabricated using quartz crystal lattice that integrated with electrochemical sensor [1]. The quartz crystal microbalance is a label free technique, which minimizes interference with the interaction being studied. A piezoelectric device is portable, simple and cost effective, and is suitable for real-time monitoring of biospecific interactions such as antigen-antibody, receptor ligand, and enzymes-substrate interactions with high sensitivity and specificity. For instance, the biological mixtures such as antibodies are capable of binding to terminal active functional groups (i.e., COOH, OH and NH2) of self-assembled monolayers (SAM) and immunocapture antigens such as glycoproptien or other targets[2]. The QCM can consequently detect mass changes due to these molecular interactions on the surface of the QCM. The top and bottom circular excitation electrodes with 150um diameter were modeled as gold (Au) films of 16μm thickness. A sinusoidal voltage with amplitude of 5 mV was applied across the quartz crystal. Figure 1 shows the principle of integrated biosensors which gold electrodes were printed on both sides of a thin 500um quartz layer to form the quartz crystal microbalance (QCM)-impedance device. The silver (Ag) semicircular counter electrode was modeled around the top working electrode on the same area of the quartz crystal for performing the electrochemical impedance spectroscopy (EIS) experiments for detection of bacteria (E-Coli) and the results were compared to quartz crystal microbalance measurements. Furthermore, the use of gold surface can be incorporated into the transducer compatible with the biological samples such as use of highly specific monoclonal antibodies, and incorporation of amplification step to maximize the signal detection. In general, the quartz crystal is traditionally considered to be a mass sensitive sensor that produces response which it changes its resonance frequency to different thin film samples or liquids in contact with it surface. For a straight relationship between a thin film mass of the order of nanograms, the quartz crystal response will be of of the order of Hertz according to Eq. 1, Sauerbrey Equation [3]. ρq and μq are the specific density and the shear modulus in quartz, respectively. ϝ0 is the fundamental resonance frequency in quartz, related to its thickness, nq. ∆m is the thin film mass deposited A, is the piezoelectrically active crystal area and n is the overtone number. Based on Eq. 1, it can be found that if the density of QCM changes, the resonant frequency of the device also changes, making the QCM suitable for monitoring changes in mass.